RAND and the Information Evolution - Ware, Willis H.; Chalk, Peter; Warnes, Richard; Clutterbuck, Lindsay; Winn, Aidan Kirby (RAND Corporation, 2023)
This professional memoir describes RAND's contributions to the evolution of computer science, particularly during the first decades following World War II, when digital computers succeeded slide rules, mechanical desk calculators, electric accounting machines, and analog computers. The memoir includes photographs and vignettes that reveal the collegial, creative, and often playful spirit in which the groundbreaking research was conducted at RAND.